ANALISIS PENGARUH FAKTOR MOTIVASI DAN FAKTOR KEPEMIMPINAN TERHADAP SEMANGAT KERJA PEGAWAI UIN MALANG - Sani, SE, M.Si.,, Achmad (IQTISHODUNA, 2007)
Work ethos is behavior managed by employee which is generally motivated to reach a set of goal. This research investigates the extent to which motivation and style in leadership impacts on the work ethos of employee. This research sets its goal to know the significant influence of motivation toward the work ethos of employee of Islamic State University of Malang.This is an explanatory research which has its goal to test defined hypothesis on the influence of motivation and style in leadership toward the work ethos of employee. The research population involves 58 administration staff of Islamic State University of Malang. The random sampling method is employed to determine the total number of the sample of the research which results in 36 administration staff. Questionnaire is used as research instruments in this research.This research employs simple linier regression and multiple linier regression to statistically analyze the data in which the coefficient determinants is set on 0,05 level. The result of the research analysis proves that motivation and style in leadership simultaneously give significant influence on the work ethos of employee with F = 51,483 and p (0,002) 0,05. Motivation partially gives significant influence toward work ethos in which p = (0,001) 0,05 and regression coefficient shows 0,339. Leadership style partially gives significant influence toward work ethos in which p = (0,000) 0,05 and regression coefficient shows 0,304.Based on the finding, it is further suggested that the policy maker in Islamic State University of Malang should give more attention to the motivation and leadership style used in the institution. It is because the result of this research proves that motivation and style in leadership simultaneously give significant influence on the work ethos of the employee. Â